كاریگه‌ری هۆكاره‌ جیۆمۆرفیه‌كان له‌ دیاریكردنی ناوچه‌ گه‌شتوگوزارییه‌كان له‌ پارێزگای هه‌ڵه‌بجه‌ به‌ به‌كارهێنانی مۆدێلی(AHP) - صابر, پ.ی.د. سایه‌ سه‌لام; عبدالله, م.ی مقداد عمر (Sulaimani Journal for Humanities, 2023)
This research indicated (the effect of geomorphic factors to determine tourist areas in Halabja Governorate using the (AHP) model, Halabja Governorate is located astronomically between two latitudes (°35 : ′27 : ′′15) and (°34 : ′53 : ′′40) north, and longitudes (°45 : ′46 : ′′24) and (°46 : ′12 : ′′2) east, and in terms of geographical location is located in northeastern Iraq and eastern Kurdistan Region, The aim of this research is to evaluate the geomorphic reasons in Halabja governorate to determine the most suitable place for tourism, there are several geomorphic factors in the region that have an important role in the formation of some forms of the earth's surface, which affected the emergence of some Attractive areas that are of great importance to the tourist activity, this research relied on the (AHP) model and the use of geographic information systems (GIS) to determine the most appropriate place for the tourist activity, and as a result the tourist areas were distributed differently in terms of the ability to attract the tourist, and the most suitable areas for tourist activity increase in valleys in mountainous areas, but the appropriate and inappropriate weak area is located in complex mountainous areas that a tourist cannot reach.